Trademark Dispute Case in International Civil Law (Case Study of PK MARI Decision No.274 PK/Pdt/2003) - Ryan, Az Zahra Nashira; Prastyanti, Rina Arum (The Easta Journal Law and Human Rights, 2025)
Brand disputes in the context of international civil law are increasing in line with the globalization of trade and rapid economic growth. This journal analyzes the Review Decision (PK) No. 274 PK/Pdt/2003 involving a trademark dispute between Prada SA, a leading fashion company from Italy, and PT Manggala Putra Perkasa in Indonesia. This study aims to explore the legal basis used by the Supreme Court in deciding this case as well as the implications of the ruling on trademark protection in international civil law. The research method used is a prescriptive legal approach whose data collection is through literature research and analysis of legal documents. The results show that the Supreme Court relies on previous jurisprudence and international treaties, such as the Paris Convention for the Protection of Industrial Property, in providing decisions in favor of the protection of well-known brands. This ruling emphasizes the importance of good faith in trademark registration and provides stronger legal protection for well-known brands than ordinary marks. The implications of this decision are very significant, the target is not only brand owners, but also consumers and stakeholders in the Indonesian business world. This increase in protection is expected to create a more favorable investment environment and increase foreign investors' confidence in the Indonesian market. This finding is expected to be a reference for policymakers and legal practitioners in an effort to strengthen the protection of intellectual property rights in Indonesia and other countries.